Histopathologic changes in the kidney tissue of Prochilodus lineatus Valenciennes, 1836 (Characiformes, Prochilodontidae) induced by sublethal concentration of Trichlorfon exposure - Marcelo Leite da Veiga; Edson de Lara Rodrigues; Fabio Juliano Pacheco; Maria José Tavares Ranzani-Paiva (Brazilian Archives of Biology and Technology, 2002)
Studies were carried out to analyse the kidney histopathological alterations of "curimbatá", Prochilodus lineatus, were analyzed. An acute bioassay was made by the water contamination with 0.2muml/l of Dipterex 500 (Trichlorfon). The kidney tissue collected after 24 hours of exposure showed an enlargement of intercapsular space with glomerular atrophy, hypertrophy of the kidney tube cells, with small granules on its cytoplasm and little nuclear alteration. Blood overflowing from capillaries with pyknotic nuclei and vacuoles in the cytoplasm it was also noticed. After 48 hours, the kidney tissue showed glomerular expansion, impossibility to visualize the intercapsular space as well as cytoplasm limit of many cells. The parietal capsular epithelium and the basal membrane presented loss of cell content, the tubular cells appeared swollen vacuolated and with thin and thick cytoplasmatic granulations. Some of the cell nuclei kept relatively regular form with a condensed chromatin on its central region, while others showed themselves relatively small and pyknotics advancing to a cariolisis and necrosis focus. Neste trabalho foram avaliadas as alterações histopatológicas no tecido renal de curimbatá Prochilodus lineatus, através de bioensaio agudo provocado pela contaminação da água por 0,2mil/litro de solução de Dipterex 500 (Trichlorfon) diluído em solução aquosa. Alterações comportamentais dos peixes pertencentes ao grupo contaminado, foram observadas a partir de 24 horas após o início da exposição. O tecido renal coletado após 24 horas de exposição apresentou aumento do espaço intercapsular com glomérulos atróficos, hipertrofia das células dos túbulos renais, extravasamento sangüíneo a partir de capilares e áreas de necrose. Após 48 horas o tecido renal apresentou dilatação glomerular, perda do conteúdo celular do epitélio capsular parietal e da membrana basal, inchaço, vacuolização e granulações finas e grossas no citoplasma das células tubulares e focos de necrose acentuada.